2017
DOI: 10.1371/journal.pone.0170764
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blinded, Randomized Comparison of Medetomidine-Tiletamine-Zolazepam and Dexmedetomidine-Tiletamine-Zolazepam Anesthesia in Free-Ranging Brown Bears (Ursus Arctos)

Abstract: We compared anesthetic features, blood parameters, and physiological responses to either medetomidine-tiletamine-zolazepam or dexmedetomidine-tiletamine-zolazepam using a double-blinded, randomized experimental design during 40 anesthetic events of free-ranging brown bears (Ursus arctos) either captured by helicopter in Sweden or by culvert trap in Canada. Induction was smooth and predictable with both anesthetic protocols. Induction time, the need for supplemental drugs to sustain anesthesia, and capture-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
6
1
Order By: Relevance
“…In the present study, the mean induction time in both groups was longer than that reported for other bear species [ 3 , 10 ]. In these previous reports, the anesthetized bears were free-ranging animals which were pursued with a helicopter.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…In the present study, the mean induction time in both groups was longer than that reported for other bear species [ 3 , 10 ]. In these previous reports, the anesthetized bears were free-ranging animals which were pursued with a helicopter.…”
Section: Discussioncontrasting
confidence: 65%
“…No bears in this study vomited or showed sign of vomiting. The advantages of combining alpha-2 agonist with tiletamine and zolazepam are a smooth and rapid induction and a smaller induction dose as previously reported in several papers [ 6 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations